Gender identity and expression in focus: The report of the United Nations Independent Expert on sexual orientation and gender identity, by Victor Madrigal-Borloz.: Published by the United Nations on 12/07/2018 United Nations official document number: A/73/152 - Chiam, Zhan; Ehrt, Julia (Torture Journal, 2018)
In his recent report, the United Nations Independent Expert on protection against violence and discrimination based on sexual orientation and gender identity, Victor Madrigal-Borloz, examines the “process of abandoning the classification of certain forms of gender as a pathology” – “depathologization”—and elaborates on the “full scope of the duty of the State to respect and promote respect of gender recognition as a component of identity” (p. 2). The report also discusses active measures to respect gender identity and concludes with a list of recommendations. While other United Nations special procedures and agencies have addressed and condemned violence and discrimination on the grounds of gender identity and expression, this report provides a deeper analysis on its root causes. It is the first special procedures report that exclusively addresses human rights with regard to gender identity and expression, and must be considered a mile-stone in the development and enunciation of international human rights law in this regard.